L-histidine utilization in Aspergillus nidulans. - Polkinghorne, M A (1982)
Histidase activity rather than uptake of L-histidine is the limiting factor for the utilization of histidine as the sole nitrogen source for Aspergillus nidulans. Histidine cannot act as the sole carbon source, and evidence is presented indicating that this is attributable to an inability to convert histidine to L-glutamate in vivo. It has been shown that this fungus lacks an active urocanase enzyme and that histidine is quantitatively converted to urocanate, which accumulates in the extracellular medium. The use of histidine as a nitrogen source is regulated by nitrogen metabolite repression control of histidase synthesis. In addition, evidence for a requirement for a carbon source for histidase synthesis and for a minor form of control by nitrate is presented. The activity of the histidase enzyme is inhibited by micromolar concentrations of the product urocanate and by physiological levels of L-glutamate and L-glutamine.